The Effect of Fiscal Policy and Macroeconomic Factors on Poverty in Districts/Cities of East Nusa Tenggara Province - Lastryanti Arnita Here; Achmad Solihin (MASI Mandiri Edukasi, 2026)
Poverty remains a persistent development challenge in East Nusa Tenggara, Indonesia, where structural constraints continue to hinder inclusive economic growth. This study investigates the impact of government expenditure (education, health, and infrastructure) and macroeconomic factors (labor absorption and economic growth) on poverty levels across 22 districts and cities in the province. Utilizing dynamic panel data covering the period 2014–2023, the analysis employs the System Generalized Method of Moments (System GMM) estimator to address endogeneity and capture poverty persistence. The empirical findings reveal strong evidence of poverty persistence, indicating a poverty trap in the region. Government expenditure in health and infrastructure significantly reduces poverty, demonstrating that targeted fiscal allocations effectively enhance productivity and lower transaction costs. In contrast, education expenditure shows a positive short-term relationship with poverty, implying a time lag before educational investments translate into tangible income improvements. Furthermore, while labor absorption significantly contributes to poverty reduction, regional economic growth has an insignificant impact, reflecting that the economic expansion in the province has not been fully inclusive. Overall, the results highlight the critical need for sustained, targeted fiscal interventions and inclusive macroeconomic policies to break the structural poverty cycle in East Nusa Tenggara.